Effect of music based cognitive behavioral therapy on mathematics test anxiety and learning outcome: Evidence from a quasi-experimental study - Echezona Gwamniru Nnamdy; Eteng-Uket Stella (Asian Journal of Education and Training, 2026)
Many learners experience mathematics test anxiety, which culminates in lower learning outcomes in the subject and ultimately undermines future career prospects, particularly in science, technology, engineering, and medicine, as well as the mental well-being of affected learners. Thus, the study aimed to assess the effectiveness of Music-Based Cognitive Behavioral Therapy (MB-CBT) in reducing test anxiety and enhancing learning outcomes in mathematics. The study adopted a quasi-experimental, non-equivalent control group design to examine a sample of 40 students with high mathematics test anxiety who were selected from one school via multistage sampling and assigned by intact classes to experimental and control groups. The experimental group of 20 randomly selected students received MB-CBT-based instruction for 8 weeks, while the control group comprised 20 randomly selected students who were conventionally taught over eight weeks as well. Analysis of covariance statistics was utilized for data analysis. Findings showed that the Music-Based Cognitive Behavioral Therapy intervention had a statistically significant effect on reducing mathematics test anxiety in students, thereby improving learning outcomes. The study shows that integrating music-imbued cognitive restructuring strategies into mathematics-related activities can serve as an effective instructional and psychological intervention for enhancing learning outcomes and reducing performance-related anxiety.